Refuse derived fuel structure for smoldering furnace - FANG XINCHENG (2014)
The utility model discloses a refuse derived fuel structure for a smoldering furnace. The refuse derived fuel structure is characterized in that the refuse derived fuel comprises a wood refuse block and a flame retardant layer arranged on the outer surface of the wood refuse block, wherein the flame retardant layer is formed by the arrangement of flame retardant particles dispersedly arranged on the outer surface of the wood refuse block, the total volume of the flame retardant particles accounts for 7%-16% of the total volume of the wood refuse block, and the distribution area of the flame retardant particles on the outer surface of the wood refuse block accounts for 68%-86% of the area of the outer surface of the wood refuse block. The refuse derived fuel structure can be used for effectively solving the problems in the prior art that as open fire easily occurs in a biomass fuel smoldering process, the conversion efficiency of fuels in the smoldering furnace is greatly reduced, and accidents are possibly ca